Media Education in Secondary Level schools and its Popularity among the Students in Sri Lanka - Raguram, S.; Wijeyananda, R. (My University, 2020)
Communication and Media Studies’ was introduced to the secondary level schools in Sri Lanka in 2004 by the Ministry of Education as an ‘optional subject’ that could be followed by the students if there is the availability of teaching staff in schools. The subject was initially commenced for grade 10 and 11 students, aiming for the General Certificate of Education (Ordinary Level). In 2008, ‘Communication and Media Studies’ was introduced to the Advanced Level students who follow Arts Stream for grades 12 and 13, the entry point to the university education. Firstly, only a few students chose ‘Communication and Media Studies’ as a subject from the basket allocated, however within a few years the number of students moved up to follow the subject. At the Advanced Level, parallel to this, ‘Communication and Media Studies’ has established itself as one of the favourite subjects in Arts Stream. The research aimed to find out the reasons and the factors that motivated students to select this subject at the Ordinary Level and highly competitive Advanced Level examination which is not only the highest examination in the secondary level of schools but also plays the role of the university entrance examination of the country through a single-window system. For this study, the data of the Department of Examinations, Sri Lanka and the school level data gathered from the National Institute of Education were collected and analyzed to explore the increasing pattern of the students selected the subject ‘Communication and Media Studies’. Furthermore, the study examined the research conducted by the undergraduate and postgraduate students of the national universities that were focused on the introduction of ‘Communication and Media Studies’ at school levels. The findings were diverse: the students attract towards the profession to work as journalists, the interest to produce media contents, become popular compare with other professions, opportunities to get novel experiences, admire to handle electronic devices, the influence of the media culture of the country, widespread of social media and chances to find self-employment through them, and finally, the facilitation to get the entrance to the universities by earning high Z- Score (Sri Lankan Entrance System to the Universities).
Keywords: Media Education; Communication and Media Studies; Secondary Level Schools; National Universities